Performance of the GRBLGru-driven Tiny Machine to Automate the Scratching and Drilling Processes - Goeritno, Arief; Wicaksono, Nugroho Adi; Irawan, Rudi; Muhidin, Muhidin; Azama, Irham Muhammad; Purwanto, Eko Hadi (Master Program in Mechanical Engineering, Gunadarma University, 2025)
This article is entirely based on a prior research article about an Arduino board-based electrical device that runs the micro-machine for printing the circuit board using GRBL-Gru software. In this article, two primary discussions relate to the research's objectives: performing the system for processing scratch and drill, selecting a spindle DC motor, and determining the necessary electrical power. The two research objectives were accomplished in stages detailed in the research methodologies. Instead of the component layouts on the PCB plate that were obtained and the electrical power needs for the axis-directed stepper motors and the DC motor for the spindle, the results of the operation tests for scratching and drilling are seen. Based on these findings, it is possible to conclude that the system's operation is consistent with the design and eventual objective of creating a tiny machine using a microcontroller to automate the scratching and drilling processes.